A consideration of the fault standard in a claim for additional compensation under s 56(1) of the Compensation for Occupational Injuries and Disease Act - Spoor, Alexander (Department of Public Law, 2016)
From initially placing the burden of injury almost exclusively on the injured employee, growing social awareness of the inherent risks in the workplace has seen an ever increasing willingness to hold the employer liable.1 This was initially driven by the courts, but developments were soon overtaken by the work of political activists and trade unions, which placed great pressure on business and the state to find more equitable systems of worker protection.2 This culminated in what is so often referred to as a new balance3 being struck in the form of comprehensive legislation to protect workers. In South Africa, this comprehensive legislation is the Compensation for Occupational Injuries and Diseases Act 3 of 1993 ('the COIDA'). The COIDA extinguishes an employee's common law rights to sue the employer for damages4 and instead introduces a no-fault system of compensation in which the employee is guaranteed an amount of compensation, when the harm from the accidents or occupational disease arises in the workplace.5 The compensation payable is in most situations significantly less to that which could be claimed at common law, being capped at a maximum of the total pecuniary loss to an employee.6 The employer thus avoids the risks associated with the possibility of costly damages claims while being obliged to fund the legislative compensation scheme through a tariff system. The tariffs payable are dependent on the risks associated with the class of industry and the safety record of the individual business.7 THE COIDA in recognition of the need to discourage employers from maintaining unsafe workplaces preserved a common law like8 fault based entitlement to what is termed 'increased compensation' under s 56 of the COIDA. 9 The significance of the provision lies in the ability of an injured employee or their dependents to claim back the difference between the no-fault compensation paid and their respective pecuniary loss.10 While potentially having a dramatic impact on the compensation received the section is completely underutilised.11 The reasons for this underutilisation are said to lie in potential claimants either being ignorant of the provisions or unable to institute claims.12 This thesis will examine the interaction between the law that regulates workmen's compensation and one aspect of how this modern system of law deals with the age old problem of negligently caused harm in the workplace. In particular, it argues that another important reason why claims for increased compensation are underutilised is because the common law defence of contributory negligence is said to apply to a claim for increased compensation. The result of this is that laws, which have since been abolished with the passing of the Apportionment of Damages Act 34 of 195613 ('the ADA') continue to apply in this one statute. The result is that cases developed over a century ago, which involved law on hobbled donkeys and steam powered trains, continues to have a major influence on whether a claim for increased compensation is successful or not.14 As will be shown, this position is untenable and a new interpretation of the provision for increased compensation is required.